Demand Analysis of Multiple Goods and Services in Vietnam - Vigani, Mauro; Dudu, Hasan (World Bank, Washington, DC, 2021)
In 1986 the Đổi Mới reform changed the economic and social policies in Vietnam, triggering steep economic growth and the shift from a low- to a middle-income economy. In parallel to the economic growth, Vietnam also experienced rapid social and demographic change, which resulted in modified consumption behavior. This paper estimates a Quadratic Almost Ideal Demand System, obtaining income and own- and cross-price elasticities for 10 groups of goods and services that can contribute to the further economic development of Vietnam. To control for potential bias generated by unobserved quality substitution and endogenous unit values, the analysis adopts an instrumental variable method. The results show that household equipment, clothing and accessories, telecommunication, transport, and medical and health services are responsive to income changes, while food, foodstuffs, beverages and tobacco, education, and electricity are income inelastic. Moreover, the analysis detects complementarity between education and the rest of the goods and services, and substitution between health care and household equipment, clothing, and telecommunication services. These results help in understanding recent socioeconomic development patterns in Vietnam and provide updated evidence to support business decisions and economic policy planning.